Central Hemodynamics in Relation to Circulating Desphospho‐Uncarboxylated Matrix Gla Protein: A Population Study - Wei, Fang‐Fei (J Am Heart Assoc, 2019)
BACKGROUND: Stiffening and calcification of the large arteries are forerunners of cardiovascular complications. MGP (Matrix Gla protein), which requires vitamin K–dependent activation, is a potent locally acting inhibitor of arterial calcification. We hypothesized that the central hemodynamic properties might be associated with inactive desphospho‐uncarboxylated MGP (dp‐ucMGP). METHODS AND RESULTS: In 835 randomly recruited Flemish individuals (mean age, 49.7 years; 45.6% women), we measured plasma dp‐ucMGP, using an ELISA‐based assay. We derived central pulse pressure and carotid‐femoral pulse wave velocity (PWV) from applanation tonometry and calculated forward and backward pulse waves using an automated, pressure‐based wave separation analysis algorithm. Aortic PWV (n=657), central pulse pressure, forward pulse wave, and backward pulse wave mean±SD values were 7.34±1.64 m/s, 45.2±15.3 mm Hg, 33.2±10.2 mm Hg, and 21.8±8.6 mm Hg, respectively. The geometric mean plasma concentration of dp‐ucMGP was 4.09 μg/L. All hemodynamic indexes increased across tertiles of dp‐ucMGP distribution. In multivariable‐adjusted analyses, a doubling of dp‐ucMGP was associated with higher PWV (0.15 m/s; 95% CI, 0.01–0.28 m/s), central pulse pressure (1.70 mm Hg; 95% CI, 0.49–2.91 mm Hg), forward pulse wave (0.93 mm Hg; 95% CI, 0.01–1.84 mm Hg), and backward pulse wave (0.71 mm Hg; 95% CI, 0.11–1.30 mm Hg). Categorization of aortic PWV by tertiles of its distribution highlighted a decreasing trend of PWV at low dp‐ucMGP (<3.35 μg/L) and an increasing trend at high dp‐ucMGP (≥5.31 μg/L). CONCLUSIONS: In people representative for the general population, higher inactive dp‐ucMGP was associated with greater PWV, central pulse pressure, forward pulse wave, and backward pulse wave. These observations highlight new avenues for preserving vascular integrity and preventing cardiovascular complications (eg, by improving a person's vitamin K status).